Morpho-Functional Changes in the Liver as a Result of Groundwater Consumption (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The task of providing the population with high-quality, and therefore safe for health, drinking water is set by the highest authorities of the country as a state priority. The task is not easy, since the quality of water supplied to the consumer is determined by many factors: the natural composition of the water source, anthropogenic impact (primarily the volume and composition of wastewater discharged into surface water sources or pumped into underground horizons), water treatment technology, reagents used, the state of utilities and so on. [1–3]. The situation is complicated in cases where a water source that does not fully meet hygienic requirements is uncontested or all water bodies in the territory are characterized by a similar chemical composition due to the natural geochemical characteristics of the area.